Estrutura e agência no meio rural : um estudo do projeto redes de referência para agricultura familiar a partir da teoria neoinstitucional - Sella, Flávia Vasconcellos (2009)
One of Brazil's main economic activities is the agriculture and cattle raising industry, so it is for its natural conditions or for its colonization process. Therefore this sector has intensive research and tecnology to help its development. But, the farm men not always adopt the practices from these researches because they not constantly recognize themselves with them, thus there is the necessity of projects and studies to adapt the research knowledge to the field. Hence Parana adopted the Projeto Redes de Referência para a Agricultura Familiar, a Government of Parana Project togheter with the Institute d'Élevage, IBRD - International Bank for Reconstruction and Development, EMATER/PR (Parana's Institute of Technical Assistence and Rural Extention) and IAPAR (Agronomic Institute of Parana). The Project chooses representative proprierties with regional characteristics and production sistems, with information about the earth, workforce and production so, from needs diagnosis, production rasing information and well fare actions for the farmers can be done. Then, from technical and economic parameters, these practices would be validated and difunded to the other units for them represented. Accordingly, in this paper, we have aimed to understand how the Projeto Redes de Referência para Agricultura Familiar has influenced the management and thechnical actions of the Parana's husbandmen, in and off the Project, from 1998 until 2009. With the Project and the farmer's action toward management and thechnical conduction presentation, it has been interpreted the structure and agency capacity of the farmers - in or off the Project. Based on the prescriptions of the Projeto Redes de Referência para Agricultura Familiar, the interviewed farmers interpretative schemas and in their actions related to the management and thechnical conduction in the period studied, under the neoinstitutional theory and the estructuration theory. These theories study how the organizations (and the rural enterprises) are connected thru technical, structural, normative and cognitive inter-dependencies, what can provoque the isomorfism, in other words, similar answers and structures and legitimated by enviromental, social and political pressures. However these answers can be diverse depending on the different institutional logics and stimulus that the organizations sufer, how they understand the changes and on the reletional context between those who propose the change and those who adopt them, besides the relationship network and the innovation adoptions filters. Meaning: the answers to the social structures depend of the interpretation that the agent has of them, while they modify or reproduce them, while they translate them to their own reality, what authors call agency capacity. With this research it can be concluded that there is agency in the actions of the majority of the farmer inside and outside the Program. And that, because the actors have agency, they produce different answers to the same stimulus, but always in a limited way and limiting the Project Structure.